2012
DOI: 10.1103/physrevb.86.125429
|View full text |Cite
|
Sign up to set email alerts
|

Structural determination of a highly stable metal-organic framework with possible application to interim radioactive waste scavenging: Hf-UiO-66

Abstract: High resolution synchrotron radiation x-ray powder diffraction (HR-XRPD) combined with Hf L3edge extended x-ray absorption fine structure (EXAFS) allowed to determine the structure of Hf-UiO-66 metal-organic framework (MOF) showing that it is iso-reticular to Zr-UiO-66 MOF [J. Am. Chem. Soc. 130, 13850 (2008)]. Thermal gravimetric measurements (coupled with mass spectroscopy) and temperature dependent synchrotron radiation XRPD proved the high thermal stability of the new MOF. The Langmuir surface area (849 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
227
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 215 publications
(239 citation statements)
references
References 100 publications
10
227
0
1
Order By: Relevance
“…23 Complete substitution of zirconium in the structure has also been reported. 16,24 MOFs containing the hexanuclear [M 6 O 4 (OH) 4 ] 12+ cluster are in fact known for a range of metal(IV) 55 cations, including Hf, U and Th. 25 For cerium(IV), the molecular hexanuclear cluster has been previously reported with sulfate, 26 acetylacetonate, 27 benzoate 28 and 1,2-phenyldiphosphonate ions.…”
mentioning
confidence: 99%
“…23 Complete substitution of zirconium in the structure has also been reported. 16,24 MOFs containing the hexanuclear [M 6 O 4 (OH) 4 ] 12+ cluster are in fact known for a range of metal(IV) 55 cations, including Hf, U and Th. 25 For cerium(IV), the molecular hexanuclear cluster has been previously reported with sulfate, 26 acetylacetonate, 27 benzoate 28 and 1,2-phenyldiphosphonate ions.…”
mentioning
confidence: 99%
“…This indicates that there may be a competitive role between BDC linkers and HCOOH modulator, and the creation of too many defects would lower the BET surface area and pore volume, resulting in lower hydrogen storage capacities. Several approaches have been undertaken to identify the structural defects within UiO-66, such as the presence of symmetry forbidden reflections in PXRD patterns [27], less weight loss than expected during thermal decomposition [28], higher surface area and pore volume than theoretically expected [29], more O-H stretching bands from FTIR spectrum [30], unexpected split and weakened fingerprints in Raman spectrum [31]. In line with the weight loss approach, thermogravimetric analysis (TGA) has been employed to identify MOF structural defects [32][33][34].…”
Section: Resultsmentioning
confidence: 99%
“…For the three systems, this combined XRPD, EXAFS and DFT approach allowed a full interpretation of the EXAFS data in both hydroxylated and dehydroxylated forms [101,102,104,105]. Please note that IR spectroscopy was crucial to confirm this model as it allowed to observe the disappearance of the O-H stretching band in these materials.…”
Section: Exafs Study On Mofs Of the Uio-66/uio-67 Family: Comparison mentioning
confidence: 90%
“…Part (g): N 2 adsorption/desorption isotherm for Hf-UiO-66 at 77 K. Unpublished figure reporting data from [100-102, 104, 105]. try studies reported in Figure 5.12c,f, UiO-67 [102] and Hf-UiO-66 [104] show thermal and chemical stability similar to that of UiO-66 and exhibit the expected surface area, as determined by low temperature volumetric N 2 adsorption isotherms ( Fig. 5.12d,g).…”
Section: Exafs Study On Mofs Of the Uio-66/uio-67 Family: Comparison mentioning
confidence: 90%